Sensibilité et esthétisme dans la pratique de l'histoire naturelle en France (XVIIIe-XIXe siècles) : un héritage de la culture de la curiosité - Marie Lemonnier (Amnis)
The representation of nature as a source of enjoyment both aesthetic and intellectual is a characteristic of the discourse on natural history in the beginning of the nineteenth century. This conception of science is often associated with romanticism as a literary movement and thus, opposed to the utilitarian discourse about nature of the Enlightenment. This article is a short reflection on the origins of this convergence between aesthetic, sensibility and science in natural history. This acknowledgment that sensibility as a part to play in science does not appear in rupture but rather in continuity with a discourse that admits pleasure and the aesthetic of nature which already exists in the eighteenth century. This discourse that insists on the alliance between utility and pleasure is observable in a « curiosity culture », which takes its roots in the practices related to natural history's cabinets and collections and also in the « curieux » and amateurs' social networks of the eighteenth century.